2020
DOI: 10.29252/jafm.13.01.30147
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of a Transonic Axial Flow Compressor with Circumferential Casing Grooves to Improve the Stall Margin

Abstract: The stability range of the gas turbine engine compressors is being challenged in the modern days due to the intention of increasing per stage maximum loading. Casing treatment has been widely adopted as a realistic passive flow control means to improve the stall margin with a slight decrease of efficiency at the same time by various grooves of which shape (location, angles and so on) has a significant influence on controlling effect. However, the influence of some details in grooves is ignored in most of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The wear of the impeller ring mainly includes impact wear and combined wear of cavitation and sediment [12,13]. The wedge grooves can increase the flow velocity near the impeller ring [14] and have a carrying effect on the fluid to sediment. Therefore, a circle of wedge grooves is set on the outside of the cover plate of the impeller to reduce the sediment concentration near the ring, as is shown in Fig.…”
Section: The Pump Studiedmentioning
confidence: 99%
“…The wear of the impeller ring mainly includes impact wear and combined wear of cavitation and sediment [12,13]. The wedge grooves can increase the flow velocity near the impeller ring [14] and have a carrying effect on the fluid to sediment. Therefore, a circle of wedge grooves is set on the outside of the cover plate of the impeller to reduce the sediment concentration near the ring, as is shown in Fig.…”
Section: The Pump Studiedmentioning
confidence: 99%
“…They stated that they reduced the deviation angle by using a diffuser with splitter blades for the high-pressure radial compressor and thus increased its performance [28]. Various numerical analysis studies have been carried out to improve the stall margin of the axial compressor [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The unsteady results indicated that the shock/tip leakage vortex interaction generated the tip leakage vortex breakdown and caused a U-type vortex, whose periodic migration along blade pressure surface led to blade loading variation and flow unsteadiness near blade tip region; the shock oscillation was observed as indication of flow unsteadiness. Ahmad et al (2020) numerically investigated the shock/tip leakage vortex interaction and the performance enhancement based on NASA Rotor 37. Result showed that shock/tip leakage vortex interaction generated a stagnation zone near blade tip region, which caused flow instability and triggered the stall.…”
Section: Introductionmentioning
confidence: 99%